Fatwa, Default, and Legal Certainty: A Study of Normative-Practical Gaps in the Resolution of Non-Performing Loans in Sharia Microfinance Institutions - Wahyuni; Salma Naqiyya Firaasya; Dwi Rachmawati; Hurin In Nurul Firdausi (Istinbath : Jurnal Hukum, 2025)
This study aims to analyze the forms of default in Islamic financing, particularly murābaḥah transactions (mutually beneficial transactions) at Baitul Māl wa Tamwīl (BMT) Adzkiya Khidmatul Ummah (AKU) in Metro City, and to examine the normative-practical gap between the settlement mechanisms applied and the provisions stipulated in the DSN-MUI fatwa. This study adopts a qualitative approach, collecting data through interviews, document analysis, and direct observation of murābaḥah financing procedures and default handling. The study’s results show significant differences between the provisions of the DSN-MUI fatwa and the operational practices of BMT. First, late fees are imposed uniformly on all problematic customers, including those who are unable to pay, while DSN-MUI Fatwa No. 47/2005 limits fines only to debtors who are able but negligent (mumāthil). Second, the allocation of penalty funds has not been disclosed transparently, contrary to the provisions of DSN-MUI Fatwa No. 04/2000, which requires clarity on fund usage. Third, there is no classification of debtor ability before sanctions are imposed. Fourth, restructuring, which is recommended as the first step in Sharia-based settlements, is only carried out after three late payments, making penalties the primary response. This study contributes empirically by presenting comprehensive evidence of normative-practical inconsistencies in sharia financing and legal certainty, and conceptually emphasizes the importance of compliance governance in achieving fairness, transparency, and compliance with sharia principles. [Penelitian ini bertujuan untuk menganalisis bentuk-bentuk wanprestasi dalam pembiyaan syariah khususnya transaski murābaḥah (transaksi saling menguntungkan) pada Baitul Māl wa Tamwīl (BMT) Adzkiya Khidmatul Ummah (AKU) Kota Metro serta mengkaji kesenjangan normatif–praktis antara mekanisme penyelesaian yang diterapkan dengan ketentuan yang diatur dalam fatwa DSN-MUI. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data melalui wawancara, analisis dokumen, dan observasi langsung terhadap prosedur pembiayaan murābaḥah dan penanganan wanprestasi. Hasil penelitian menunjukkan adanya perbedaan signifikan antara ketentuan fatwa DSN-MUI dan praktik operasional BMT. Pertama, denda keterlambatan dikenakan secara seragam kepada seluruh nasabah bermasalah, termasuk yang tidak mampu membayar, sementara Fatwa DSN-MUI No. 47/2005 membatasi denda hanya untuk debitur mampu tetapi lalai (mumāthil). Kedua, alokasi dana denda belum disampaikan secara transparan, bertentangan dengan ketentuan Fatwa DSN-MUI No. 04/2000 yang mewajibkan kejelasan penggunaan dana. Ketiga, tidak terdapat klasifikasi kemampuan debitur sebelum penetapan sanksi. Keempat, restrukturisasi yang direkomendasikan sebagai langkah awal penyelesaian berbasis syari’ah baru dilakukan setelah tiga kali keterlambatan sehingga denda menjadi respons utama. Penelitian ini berkontribusi secara empiris dengan memaparkan bukti komprehensif mengenai ketidaksesuaian normatif–praktis dalam pembiyaan syariah dan kepastian hukum, serta secara konseptual menegaskan pentingnya tata kelola kepatuhan untuk mewujudkan keadilan, transparansi, dan kesesuaian prinsip syariah].